A three-tier model of reading instruction supported by technology. (1st April 2011) - Chambers, Bette; Abrami, Philip; Slavin, Robert; Madden, Nancy
The reading performance of poor and minority children is far below that of more advantaged children in most developed countries. Several comprehensive school reform strategies have been found to significantly improve children's achievement but more effective, replicable models are needed to significantly reduce reading gaps. This article describes an evidence-based, technology-supported literacy programme that integrates core classroom instruction, follow-up small-group remedial support, and one-to-one tutoring for struggling readers. This three-tier model has been developed by revising the Success for All reading programme to create a technology-based programme that is presented on interactive whiteboards, supported by two computer-assisted tutoring programs to support struggling readers.